Business Environment Dynamics and Adaptive Strategies for Sustainability A Case Study of a State-Owned Meat Processing Company in Jakarta: Dynamics and Adaptive Strategies for Sustainability - Rendy Riyanto; Sri Wahyuni (Jurnal Penelitian, 2025)
Objective: This study aims to analyze the dynamics of the business environment and formulate adaptive strategies focused on sustainability for a state-owned beef processing company. Specifically, this research examines the impact of sustainable operational management on environmental and financial performance. Findings: The analysis shows that high waste ratios and a lack of real-time technology are internal weaknesses that can be addressed. The implementation of adaptive strategies has significant potential to improve environmental performance (waste and carbon footprint reduction) and financial performance (cost efficiency). Originality/Value: This study offers a unique contribution by integrating business environment analysis, operational strategy, and performance impacts into a single, coherent framework, specifically within the context of the meat processing industry in a developing country. Practical/Policy Implications: The results of this study offer practical guidance for managers in designing efficient and sustainable operational strategies. For policymakers, these findings can serve as a basis for formulating regulations and incentives that encourage the industry to adopt more responsible and competitive business practices.